Antimicrobial effect of an ultrasonic levitation washer disinfector with silver electrolysis and ozone oxidation on methicillin‐resistant Staphylococcus aureus. Issue 12 (4th December 2013) - Tamai, Mariko; Matsushita, Shigeto; Miyanohara, Hiroaki; Imuta, Naoko; Ikeda, Ryuji; Kawai, Kazuhiro; Nishi, Junichiro; Sakamoto, Akihiro; Shigihara, Takanori; Kanekura, Takuro
Abstract Methicillin‐resistant Staphylococcus aureus (MRSA) has rapidly emerged as a cause of severe and intractable skin infection. At present, there are no effective topical treatments, and infection or colonization by MRSA of the skin raises serious medical problems. We developed an ultrasonic levitation washer that generates silver ions (Ag+) and ozone (O3) to clean and sterilize medical devices. We report the effect of ultrasonic levitation (levitation) with Ag+ and O3 on MRSA in vitro and in vivo. Antimicrobial effect against six MRSA strains of all agr types was examined under three in vitro conditions; cells floating in a water tank, cells infiltrating‐, and cells forming a biofilm on an atelocollagen membrane. In the in vivo studies, we assayed the number of MRSA organisms that survived treatment on murine skin ulcers and evaluated the ulcer size. Levitation with Ag+ dramatically decreased the survival of MRSA floating in a water tank. Levitation with Ag+ and O3 significantly decreased the viability of MRSA that had infiltrated or formed a biofilm on atelocollagen membranes regardless of the level of biofilm production. In vivo studies showed that the number of MRSA on murine skin ulcers was significantly decreased when 15‐min treatment was performed for 7 consecutive days and that the ulcer size was significantly decreased after the seventh treatment course. Levitation with Ag+ and O3 may be a valuable tool for treating MRSA infestation of the skin and for accelerating wound healing.